2015
DOI: 10.1111/psyp.12499
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic/racial differences in the association between social support and levels of C‐reactive proteins in the North Texas Heart Study

Abstract: Perceived social support has been reliably related to lower rates of morbidity and mortality. However, studies modeling C-reactive protein (CRP) as an important biological pathway linking social support to health have produced inconsistent results. Given purported ethnic/racial differences in sensitivity to social resources, the present study tested if ethnicity/race moderated the link between perceived support and CRP in a diverse community sample of 300 participants from the North Texas Heart Study. Consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 60 publications
(89 reference statements)
1
21
0
Order By: Relevance
“…Finally, our sample was comprised of mostly Caucasian mothers (69.2%) and was therefore limited in racial/ethnic diversity. Recent evidence has emerged suggesting possible differences across racial/ethnic groups in patterns of chronic inflammation indexed via CRP, especially in social contexts (i.e., perceived social support predicting lower levels of CRP in African Americans; Uchino et al, ). Future research should consider ethnicity/race when examining CRP in social contexts as there are often significant sociocultural differences across groups, particularly in the family environment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our sample was comprised of mostly Caucasian mothers (69.2%) and was therefore limited in racial/ethnic diversity. Recent evidence has emerged suggesting possible differences across racial/ethnic groups in patterns of chronic inflammation indexed via CRP, especially in social contexts (i.e., perceived social support predicting lower levels of CRP in African Americans; Uchino et al, ). Future research should consider ethnicity/race when examining CRP in social contexts as there are often significant sociocultural differences across groups, particularly in the family environment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the sample reflected significant income diversity with 12% reporting a household income less than $20,000, 10% above $150,000, and the modal annual household income reported to be $75,000 to $100,000. Detailed demographics are reported elsewhere (19). …”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that CRP predicts an increased risk of coronary heart disease [Danesh et al, ; Danesh et al, ; Buckley et al, ; Kaptoge et al, ]. Some community‐based studies have found an association between high social support and lowering high sensitivity CRP (hs‐CRP) levels [Ford et al, ; Loucks et al, ; Mezuk et al, ; Glei et al, ; Uchino et al, ].…”
Section: Introductionmentioning
confidence: 99%